Three regimens for re-treatment failure of Sofosbuvir-based therapy for chronic hepatitis-C genotype-4: a cohort study - Shousha, Hend Ibrahim (2022)
Despite the high sustained virologic response (SVR) rates of direct-acting antiviral (DAAs) therapy, a small number of patients does not eradicate the virus, and these patients represent a challenge. This study aims to compare the outcomes of three second-line regimens for DAAs-experienced patients with chronic hepatitis C (CHC). This prospective observational study was conducted at the Damanhur Viral Hepatitis Center from January 2017 to February 2020. We included patients with CHC who did not achieve SVR after the complete course of Sofosbuvir/Daclatasvir±Ribavirin (SOF/DAC±RBV). The primary endpoint was SVR-12 after re-treatment. This study included 360 patients (with a mean age of 51.53±11.38 years). Approximately 51.1% of the patients were males, and 65.5% had liver cirrhosis. All patients of group 1 (45 patients) received SOF/VEL/VOX over 12-weeks; SVR-12 was achieved in 44 patients (97.8%). Group 2 (28 patients) received SOF/DAC/RBV over 24-weeks; (one patient was lost during follow-ups and one patient discontinued treatment due to hepatic decompensation). SVR-12 was achieved in 25 patients (96.2%). Group 3 (287 patients) received SOF/Ombitasvir/Paritaprevir/Ritonavir/RBV) over 12-weeks. Eight patients were lost during follow-ups, and one patient discontinued treatment due to grade 4 adverse events. SVR-12 was achieved in 276 patients (99.3%). There was no difference between the groups regarding their age, gender distribution, baseline viral load or comorbidities. Adverse events (thrombocytopenia, anemia, hyperbilirubinaemia and prolonged INR) were significantly higher in group 3, while group 1 did not experience any. The three studied retreatment regimens can be used for DAAs treatment-experienced patients considering availability. The SOF/VEL/VOX combination had the least adverse events.